Organização da atenção nutricional na atenção primária à saúde para o enfrentamento da obesidade em Mato Grosso - Paiva, Rafaela Dias (2022)
Obesity is considered a global epidemic, due to its multifactorial nature and complexity, it represents a challenge within the SUS in Brazil. Objective: To map the organization of nutritional care to face obesity and NCDs in Mato Grosso. Methods: descriptive observational study. Data collected through a virtual, self-administered questionnaire proposed by the Ministry of Health aimed at health managers/secretaries, and PHC health professionals. Sample of 130 municipalities, and 542 UBS. Result: only 8% of responses were obtained from management; it is observed that there is no municipal coordination of food and nutrition, the area of food and nutrition does not participate in decision-making processes or management planning (60%); municipalities do not have nutritional therapy protocols. Only 30% make use of SISVAN, and perform VAN actions. The participation of assistance corresponded to 14% of the sample, only 30% analyze data from users of the territory, 9% discuss the indicators; 24% refer to integrate some plan to organize the LCSO; 58% regulate access to specialized care, and have a referral protocol; 12% say there is an organized LCSO in their health region. Managers and professionals do not have training on obesity. Conclusion: Despite the low participation of municipalities, there is a long way to go for the realization of the organization of the ATN of actions in PHC. The need for more research on the subject is encouraged, however, it is hoped that this study will support the strengthening of public policies for the establishment of the LCSO in the municipalities.